An overlooked horticultural crop, Smyrnium olusatrum, as a potential source of compounds effective against African trypanosomiasis. Issue 2 (April 2017) - Petrelli, Riccardo; Ranjbarian, Farahnaz; Dall'Acqua, Stefano; Papa, Fabrizio; Iannarelli, Romilde; Ngahang Kamte, Stephane L.; Vittori, Sauro; Benelli, Giovanni; Maggi, Filippo; Hofer, Anders; Cappellacci, Loredana
Abstract: Among natural products, sesquiterpenes have shown promising inhibitory effects against bloodstream forms of Trypanosoma brucei, the protozoan parasite causing human African trypanosomiasis (HAT). Smyrnium olusatrum (Apiaceae), also known as Alexanders or wild celery, is a neglected horticultural crop characterized by oxygenated sesquiterpenes containing a furan ring. In the present work we explored the potential of its essential oils obtained from different organs and the main oxygenated sesquiterpenes, namely isofuranodiene, germacrone and β-acetoxyfuranoeudesm-4(15)-ene, as inhibitors of Trypanosoma brucei . All essential oils effectively inhibited the growth of parasite showing IC50 values of 1.9–4.0 μg/ml. Among the main essential oil constituents, isofuranodiene exhibited a significant and selective inhibitory activity against T. brucei (IC50 of 0.6 μg/ml, SI  = 30), with β-acetoxyfuranoeudesm-4(15)-ene giving a moderate potentiating effect. These results shed light on the possible application of isofuranodiene as an antiprotozoal agent to be included in combination treatments aimed not only at curing patients but also at preventing the diffusion of HAT. Graphical abstract: Highlights: Smyrnium olusatrum essential oils were evaluated against Trypanosma brucei . Their inhibitory activity was noteworthy (IC50 range was 1.9–4.0 μg/ml). The most active oil component was isofuranodiene (IC50 0.65 μg/ml). β-Acetoxyfuranoeudesm-4(15)-ene increased the parasite sensitivity. Germacrone was ineffective against the parasite.